Hubungan Antara Koordinasi Mata Tangan dengan Kualitas Pukulan pada Atlet Woodball Provinsi Bali - Ketut Juliati; M. Widnyana; Govinda Vittala; Ni Luh Putu Gita Karunia Saraswati (OBAT: Jurnal Riset Ilmu Farmasi dan Kesehatan, 2025)
Woodball was first introduced in 2006 and has since grown rapidly across the country. In addition, many woodball clubs and communities have emerged, and woodball has become an officially recognized competitive sport since 2016. In 2016, woodball even became part of the national sports week (PON) in West Java. Woodball is a sport that combines elements of golf and croquet, emphasizing the accuracy of shots to pass through the goal with a wooden ball. Hand-eye coordination is one of the key factors that can influence the quality of an athlete's shots. Objective: To determine the relationship between hand-eye coordination and shot quality in woodball athletes in Bali Province. An observational analytical study with a cross-sectional approach involving 42 woodball athletes in Bali Province. Hand-eye coordination was measured using a 30-second ball catch-and-throw test, while shot quality was assessed using a skill test based on the number of balls successfully passing through the gate. Analysis was performed using Spearman's rho correlation test. The analysis revealed a significant relationship between eye-hand coordination and swing quality in woodball athletes (P < 0.05). The positive correlation coefficient indicates that better eye-hand coordination leads to higher swing quality. There is a significant relationship between eye-hand coordination and shot quality. Improving visual-motor coordination skills can contribute to the performance of woodball athletes.